Enantioselective Nitroso Aldol Intramolecular Transesterification Cyclization Domino Reaction for Highly Effective Construction of Chiral Spirooxindoles. Issue 32 (12th October 2016) - Ji, Shan‐Ping; Liu, Lin‐Wei; Chen, Feng; Ren, Hong‐Xia; Yang, Yu; Zhang, Zheng‐Bing; Peng, Lin; Wang, Li‐Xin
Abstract : A catalytic asymmetric nitroso aldol intramolecular transesterification cyclization domino reaction between a C3 alkyl ester substituted oxindole and nitrosobenzene for the construction of chiral spirooxindoles was achieved in the presence of a chiral bifunctional tertiary amine thiourea catalyst and water. Optically active spirooxindoles were obtained in moderate yields (up to 76 %) and excellent enantioselectivities (up to 95 % ee ). Abstract : Catalytic asymmetric nitroso aldol intramolecular transesterification cyclization domino reaction of a C3 alkyl ester substituted oxindole and nitrosobenzene to construct optically active spirooxindoles was achieved by using a chiral bifunctional tertiary amine thiourea as catalyst and water as additive in moderate yields (up to 76 %) and high enantioselectivities (up to 96 % ee ).